Evaluation of the effect of the application of two types of potassium fertilizers on the production and quality of ungrafted Isabel’ grapes - Fugalli, Maurício; Silvestre, Wendel Paulo; Fernandes Pauletti, Gabriel (Revista Interdisciplinar de Ciência Aplicada, 2023)
Potassium is a macronutrient responsible for regulating plants' metabolic processes and water balance. In grapevines, this nutrient strongly influences the production and quality parameters of the berries, consequently affecting the quality of the juices and wines produced. Potassium can be supplied differently, impacting vineyard productivity and grape properties. The present study aimed to evaluate the effect of applying two different fertilizers on the production and quality of ungrafted Isabel vines. The experiment was carried out in the 2016/2017 cycle in the Serra Gaúcha region. Three treatments were tested: control without fertilization (T1), addition of 80 kg∙ha-1 of K2O in the form of KCl, and addition of 80 kg∙ha-1 of K2O as the compound fertilizer form 04-18-08 (N-P-K). Yield per plant, potassium content in leaf petioles, soluble solids, titratable acidity, SS/TA ratio, must pH, and total phenolic compounds and anthocyanins content were determined. The results showed that fertilization did not influence the yield per plant nor the soluble solids content, regardless of the fertilizer used. The application of KCl caused a reduction in the titratable acidity, with a consequent increase in the SS/TA ratio. On the other hand, applying the 04-18-08 fertilizer promoted a growth in the total anthocyanin content and pH without affecting the titratable acidity. According to the results, the studied fertilizers can be used in the vine culture without damage to the productivity of the plants or the quality of the berries. Considering the use of these fruits as a feedstock for wines and juices, the 04-18-08 fertilizer would be an interesting option aiming to increase the contents of bioactive compounds, such as anthocyanins.